Transit-Oriented Development in Teresina, Piauí - Chaves , Cândida Maria Barbosa Feitosa Silva; Santos , Laudenides Pontes dos (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
Transit-Oriented Development – TOD is an urban planning and landscape strategy which goals are to organize compact neighborhoods with high demographic density, land use diversity, and the offering of public services and space to provide socializing and reduce car dependency. This paper goals to evaluate the potential of sustainable development according to TODs principles, in transport corridor “Avenida João XXIII”, located in Teresina, Piauí, Brazil. Besides that, this paper also goals to evaluate the adherence scale of Teresina’s urban policy to TODS principles and objectives. To this end, the methodological procedures include exploratory research of the bibliographic and documentary type, in addition to quantitative and qualitative research composed of observational and statistical methods. The time frame to be worked on is contemporaneity, using databases from the Census/IBGE (2010) and information from the Municipal Transport and Traffic Superintendency (STRANS) and the Municipal Planning Secretariat (SEMPLAN). The results demonstrate that the corridor Av. João XXIII has high potential for sustainable transport-oriented development. The TODS potential evaluation may be able to orientate actions and real estate investments of the public and private sectors in order to transform the urban space by the improvement of the transportation infrastructure, environmental sanitation and by offering more efficient public services; besides that, may be able to minimize the urban voids, bringing live and movement to the streets, what may contribute to minimize the urban violence rates and to the improvement of the life quality.